An introduction to mathematical models of coagulation-fragmentation processes: a discrete deterministic mean-field approach - Wattis, Jonathan A.D. (Elsevier, 2006)
We summarise the properties and the fundamental mathematical results associated with basic models which describe coagulation and fragmentation processes in a deterministic manner and in which cluster size is a discrete quantity (an integer multiple of some basic unit size). In particular, we discuss Smoluchowski's equation for aggregation, the Becker-Döring model of simultaneous aggregation and fragmentation, and more general models involving coagulation and fragmentation.